2021
DOI: 10.5294/laclil.2021.14.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions on the Use of Project-Based Learning in CLIL: Learning Outputs and Psycho-Affective Considerations

Abstract: The Content and Language Integrated Learning (CLIL) approach has become one of the most frequent teaching options used as a pivotal element of bilingual programs. Over the last two decades, a lot has been written about its characteristics, its potential, and the methodological approaches that should be used to encourage such programs. Since the main objective of CLIL is to improve the use of the foreign language as a vehicle for communication by students when accessing and manipulating content matter, it seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Several previous studies found that CLIL was effective and suitable to promote students' English language competencies and contribute to the effectiveness of the teaching and learning process (Delgado-Gutierrez, 2020;Lastra-Mercado, 2016;Sánchez-García & Pavón-Vázquez, 2021;Vasquez, 2019). Even the combination of CLIL with another teaching method like Project-based Learning (PjBL) would also help students to face the future's challenges (Sanz Navarro, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Several previous studies found that CLIL was effective and suitable to promote students' English language competencies and contribute to the effectiveness of the teaching and learning process (Delgado-Gutierrez, 2020;Lastra-Mercado, 2016;Sánchez-García & Pavón-Vázquez, 2021;Vasquez, 2019). Even the combination of CLIL with another teaching method like Project-based Learning (PjBL) would also help students to face the future's challenges (Sanz Navarro, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…PjBL can be briefly defined as educational education that involves the acquisition of knowledge and skills through the process of producing and completing a project (Sánchez-García & Pavón-Vázquez, 2021). Various studies have been conducted using PjBL as a learning method for skill development (Rohm, 2021), creative problem solving (Chen & Chan, 2021), student attitudes (Parker, 2020), interpersonal competence development (Crespí et al, 2022), project-based earning with interdisciplinary approach (Hart, 2019), collaboration in PjBL (Hussein, 2021), group work orientation through PjBL (Jaiswal et al, 2021), students perception in psycho affective through PjBL (Sánchez-García & Pavón-Vázquez, 2021), and so on. Furthermore, Sánchez-García and Pavón-Vázquez (2021) explain that PjBL presents a new approach in pedagogy that emphasizes collaboration and cooperation among students.…”
Section: Introductionmentioning
confidence: 99%